An epidemiological approach to comorbidities in patients with COPD - Siraj, Rayan (2021)
Chronic Obstructive Pulmonary Disease (COPD) is associated with comorbidities. Cardiovascular (CV) disease, cognitive impairment, dementia, and depression are common comorbidities in patients with COPD, leading to increased morbidity and mortality. However, there are considerable gaps in how these comorbidities are assessed, while the burden of others remains inadequately researched.